Palliative treatment of cancer anorexia with oral suspension of megestrol acetate - Tomíska, M; Tomisková, M; Salajka, F; Adam, Z; Vorlícek, J (Neoplasma, 2003)
Megestrol acetate (MA) is a progestational agent, currently known as one of the most effective appetite stimulants in patients suffering from cancer anorexia/cachexia syndrome. Oral suspension of this drug may be particularly useful in patients with far advanced disease, where taking larger amount of pills may lead to the decrease of patient compliance. The influence of oral MA suspension on quality of life and nutritional status was evaluated in 22 patients with far advanced cancer suffering from anorexia and more than 5 per cent weight loss, all beyond the scope of anticancer treatment. Most patients had lung or gastrointestinal cancer. QLQ-C30 questionnaire, visual analogue scale (VAS) for appetite, anthropometry, maximal handgrip strength and laboratory data were obtained before treatment and then after 2, 4, and 8 weeks of therapy. Despite of a known high mortality in this prognostically unfavorable group of patients (36% within two months in this study), overall quality of life after the daily dose of 480-840 mg of MA was improved in 63, 56, and 55% of patients remaining on therapy after 2, 4, and 8 weeks, respectively. Appetite was the most successfully influenced parameter with an improvement in VAS in 95% of cases after 2 weeks of therapy (p=0.0001). The drug was well tolerated by the great majority of patients. Oral suspension of megestrol acetate maybean effective palliative treatment for many patients with far advanced cancer suffering from anorexia/cachexia syndrome.
Keywords: dospělí; suspenze; chuť k jídlu; Palliative Care; průzkumy a dotazníky; Female; nechutenství; paliativní péče; Quality of Life; Adult; ženské pohlaví; Surveys and Questionnaires; Neoplasms; nádory; Appetite Stimulants; kvalita života; Nutritional Status; lidé; Suspensions; megestrolacetát; Anorexia; nutriční stav; tělesná hmotnost; Male; Appetite; Aged; aplikace orální; Body Weight; lidé středního věku; Megestrol Acetate; senioři; mužské pohlaví; Administration, Oral; chuťová stimulancia; Middle Aged; Humans